Improving the electrochemical performance of LiNi1/3Co1/3Mn1/3O2 cathode material via tungsten modification. (20th February 2019) - Luo, Bi; Jiang, Bing; Peng, Peng; Huang, JiaJia; Chen, Jiewei; Li, Meicheng; Chu, Lihua; Li, Yingfeng
Abstract: Poor rate capability and capacity degradation of LiNix Coy Mnz O2 restricts its practical commercial applications at high operating voltage (>4.3 V). LiNi1/3 Co1/3 Mn1/3 O2 is successfully modified by tungsten compound through a cost-effective ball-milling and annealing process. The rate capability of W-modified cathode is increased by 57.6% at 10C in 3.0–4.5 V. Moreover, after 100 cycles the capacity retention is improved from 80% to 96% under 0.5C. At 1C, W-modified cathode still maintains 145 mAh g −1 discharge capacity after 100 cycles, which has 16% increase than pristine LiNi1/3 Co1/3 Mn1/3 O2 . The improvements on rate and cycle performance are introduced by enhanced Li-ion diffusion and surface stability by tungsten modification. Highlights: LiNi1/3 Co1/3 Mn1/3 O2 is modified via tungsten compounds. The tungsten compounds forms via a cost-effective ball-milling and annealing process. The W-modified cathode battery delivers an enhanced capacity and rate capability at a high operating voltage. The modification method enhances Li-ion diffusion and surface stability.